Prognostic factors in patients with breast cancer and brain metastasis as the first site of recurrence - Alejandro Mohar-Betancourt; Alberto Alvarado-Miranda; Juan Alejandro Torres-Domínguez; Paula Cabrera; Fernando Lara Medina; Yaudim Sadid Villarreal-Gómez; Nancy Reynoso-Noverón (Instituto Nacional de Salud Pública, 2018)
Objective. To evaluate the prognostic factors (clinicalpathological characteristics and treatments) in patients with breast cancer and metastasis to central nervous system (CNS) as the first site of the disease. Materials and methods. Kaplan-Meier method and life tables were used to estimate overall survival time over a retrospective cohort of 125 breast cancer patients treated at the Instituto Nacional de Cancerología (INCan) during 2007-2015, who presented metastasis to the CNS as the first site of extension of the disease. The cox proportional hazards model was used to determine the prognosis factors. Result. The median overall survival time was 14.2 months (IC95%: 11.83-26.93). Patients with triple negative (TN), according to inmunohistochemistry analysis classification, had lower survival times (p=0.0004) and had a risk of dying two times (p=0.037) higher than patients with a different immunophenotype (HR: 2.77. 95%CI: 1.10-6.99). The degree of intermediate SBR increases the risk of dying in patients with metastasis (HR 2.76, 95% CI: 1.17-6.51). Conclusion. CNS metastasis continues to be a poor prognostic factor that reduces survival and affects quality of life. It is recommended to monitor the early presence of clinical neurological manifestations during follow-up for prompt treatment. TN patients have worse prognosis and HER2+ a better control.